2016
DOI: 10.1002/mats201500072
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Computational and Experimental Study of Copolymerization Propagation Kinetics for 1‐Ethylcyclopentyl methacrylate and Methyl methacrylate

Abstract: The crosspropagation of 1-ethylcyclopentyl methacrylate (ECPMA) and methyl methacrylate (MMA) has been studied using a combination of quantum chemistry calculations and experiment. Our computational work utilizes a trimer-to-tetramer reaction model, coupled with an ONIOM (B3LYP/6-31G(2df,p): B3LYP/6-31G(d)) method for geometry optimization and an M06-2X/6-311+G(2df,p) method plus SMD solvation model for single point energy calculations. The results show several trends: the identity of the ultimate unit of a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Hence, the cumulative and instantaneous mole fractions in the copolymer are about the same. This experimental fact (and subsequent analysis) is considered "best practice," and is used throughout the reactivity ratio estimation literature (see, for example, [10,[12][13][14]16,17]). …”
Section: Samplementioning
confidence: 99%
“…Hence, the cumulative and instantaneous mole fractions in the copolymer are about the same. This experimental fact (and subsequent analysis) is considered "best practice," and is used throughout the reactivity ratio estimation literature (see, for example, [10,[12][13][14]16,17]). …”
Section: Samplementioning
confidence: 99%
“…The reasons of the formation of alternate polymers by MA and olefins are still unclear in detail. The methods of quantum chemistry based on the density functional theory were successfully used for the analysis of different radical polymerization processes [50][51][52], including homo-and copolymerization of acrylates [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], acrylamides [70,72,73], and acrylonitrile [74]. However, as far as we know, DFT-based methods have not been extensively used for visualization and comprehensive analysis of the free radical alternating copolymerization of donor and cyclic acceptor monomers, except the publications of Matsumoto et al, devoted to the copolymerization of N-methylmaleimide (MMI) with olefins [75], and MA with 2,4-dimethylpenta-1,3-diene [76].…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity ratios that characterize x MA/ x MA copolymerizations are typically near unity meaning that both x MA react with equal addition probabilities. This is true for simple systems like MMA/DMA, but also for x MA bearing diverse functional groups in their ester side chains such as 2-(2-bromopropionyloxy) propyl methacrylate, AAEMA, or 1-ethylcyclopentyl methacrylate . Furthermore, a variety of x MA/ n -alkyl acrylate ( x A) pairs consistently produce methacrylate-rich copolymers. ,,, For such x MA/ x MA and x MA/ x A copolymerization systems, it is found that the effect of solvent choice on copolymer composition is small as long as the difference in monomer and solvent polarities is not large. , As summarized by Figure , the H-bonding capabilities of the HEMA/BMA and HEMA/BA systems cause copolymer composition to deviate from their respective expected behaviors.…”
Section: Effect Of Hydrogen Bonding On Copolymer Compositionmentioning
confidence: 98%